Answer:
![l'(\theta) = (1)/(\sigma^2) \sum_(i=1)^n (X_i -\theta)](https://img.qammunity.org/2021/formulas/mathematics/college/yukj3h0zr5o4fj640v66yp24vlfbgl0501.png)
And then the maximum occurs when
, and that is only satisfied if and only if:
![\hat \theta = \bar X](https://img.qammunity.org/2021/formulas/mathematics/college/un88dajzkr2geajkmjfl9rport5ht5dtks.png)
Explanation:
For this case we have a random sample
where
where
is fixed. And we want to show that the maximum likehood estimator for
.
The first step is obtain the probability distribution function for the random variable X. For this case each
have the following density function:
![f(x_i | \theta,\sigma^2) = (1)/(√(2\pi)\sigma) exp^{-((x-\theta)^2)/(2\sigma^2)} , -\infty \leq x \leq \infty](https://img.qammunity.org/2021/formulas/mathematics/college/5kwmv45x11psfezgpa7xvrtrvx0h1w67gh.png)
The likehood function is given by:
![L(\theta) = \prod_(i=1)^n f(x_i)](https://img.qammunity.org/2021/formulas/mathematics/college/ezk2ugm6hk1p7jcl9bu879eadnk5vf6u59.png)
Assuming independence between the random sample, and replacing the density function we have this:
![L(\theta) = ((1)/(√(2\pi \sigma^2)))^n exp (-(1)/(2\sigma^2) \sum_(i=1)^n (X_i-\theta)^2)](https://img.qammunity.org/2021/formulas/mathematics/college/ybsfk3gv059v0vq6ix4kly5yx118sgcqar.png)
Taking the natural log on btoh sides we got:
![l(\theta) = -(n)/(2) ln(√(2\pi\sigma^2)) - (1)/(2\sigma^2) \sum_(i=1)^n (X_i -\theta)^2](https://img.qammunity.org/2021/formulas/mathematics/college/gn5z7ij51bb7e10fh8r007ahirz6rri3ll.png)
Now if we take the derivate respect
we will see this:
![l'(\theta) = (1)/(\sigma^2) \sum_(i=1)^n (X_i -\theta)](https://img.qammunity.org/2021/formulas/mathematics/college/yukj3h0zr5o4fj640v66yp24vlfbgl0501.png)
And then the maximum occurs when
, and that is only satisfied if and only if:
![\hat \theta = \bar X](https://img.qammunity.org/2021/formulas/mathematics/college/un88dajzkr2geajkmjfl9rport5ht5dtks.png)